Disponibilidade hídrica em reservatórios no semiárido brasileiro: interações entre assoreamento e escassez - Lopes, José Wellington Batista (2016)
The available water resources, in the Brazilian semiarid, depend on the available discharge from the local reservoirs. Therefore, when managing water resources, its use must be most judiciously granted, given that the prevailing natural conditions make the system particularly vulnerable to water scarcity. Considering this, the present work is centered on methods which allow better management of surface water resources in the Brazilian Semi-Arid, considering fundamental aspects, such as water availability reduction (due to alluviation) and water scarcity (due to droughts). This approach made necessary to divide the work in three phases, corresponding to one chapter each. The initial chapter presents a simplified method for bathymetric survey (aided by remote sensing) and evaluates the errors obtained using this method to calculate the long-term water availability. The proposed method is applied to the Pentecoste reservoir (current maximum storage capacity: 360 hm³). The second chapter presents a modified hydrological drought index, which allows the evaluation of alluviation impact on water availability. The proposed modification focuses on evaluating reservoir discharge. Two reservoirs are analyzed in this chapter, the Marengo (current maximum storage capacity: 15.3 hm³) and the Pentecoste . In the last chapter, the effective water availability in multi-annual droughts, under different reservoir operating rules (and taking into account reservoir alluviation since construction ) is evaluated. Three reservoirs with storage capacity of different orders of magnitude are analyzed: Marengo (15 hm³), Pentecoste (360hm³) and Orós (1956 hm³). The results from Chapter I support the conclusions that: (i) From the application of the simplified bathymetric method with remote sensing, it is possible to estimate the storage capacity and to evaluate (update) the height-area-volume curves of the reservoirs with an error margin of up to 10%; (ii) The simplified method had its alluviation estimate deviate by almost 100% (from measurement), indicating that it is not adequate for assessing the alluviation itself; (iii) Estimation of water availability shows good results (average error below 4%) when using data from the proposed simplified method;(iv) The high deviation of the estimated alluviation values does not extend to the estimated water availability, indicating that the proposed technique can be applied for water management purposes. In Chapter II, it is concluded that: (i) The proposed modification in the analysis of reservoir discharge in periods of severe drought is unprecedented, since it quantifies the alluviation impact on a hydrological drought index; (ii) The change in the time step of the water balance of the hydrological drought index (monthly to annual), does not cause significant changes in the drought variable that can show evidence of alluviation effect; (iii) It was verified that alluviation intensifies the already deleterious drought effects, but it was not possible to observe variations of risk class, for instance, one in which a drought of moderate severity evolves into another one of higher severity. The last stage of this research allows to conclude that: (i) effective water availability in the period of scarcity presents a positive correlation with the reservoir maximum storage capacity, indicating that larger reservoirs tend to be less vulnerable to multiannual droughts; (ii) The severity level of the multiannual drought is decisive in reducing the regularizable discharge; (iii) The regularizable discharges associated with the lower water security (security levels evaluated: 99, 95, 90 and 85%) show greater losses due to severity intensification on a multiannual drought; (iv) The rigidity of the operational rule of the reservoir has an inverse relationship with the effective water availability, ie, the more rigid the operation (ie, the earlier the rationing starts), the lower the available discharge for a given security level ; (v) Alluviation has relevant impact on the effective water availability in times of severe droughts (multiyear droughts) in the Brazilian semiarid region.